Behavioral insights on organ donation: How can behavioral economics contribute to the deficit of organs for transplantation - Fonseca, Patricia (Brazilian Journal of Transplantation, 2017)
Recent data shows that 43% of the families in Brasil still do not autorize organ donation. Therefore understanding which variables play a role at this moment and the complex decision-making process on organ donation is necessary so that new efforts seeking to raise families consent in the country can be implemented. This present work aims: a) to introduce behavioral concepts with the potential to enrich our understanding about the decision making process on organ donation like framing, status quo, social norms, inertia and procrastination; b) to bring forward experiments and public policies already applied worldwide inspired in this behavioral concepts and its results. This reflexive study is based on the Behavioral Economics findings. We conclude from this current reflection that these behavioral concepts present relevant explanatory potential. To incorporate them in the decision-making process model indicates not only a possible contribution to families approach, but also to the construction of campaigns and in the future for a better choice architecture design (nudge).